Efficient Extraction of the RuBisCO Enzyme from Spinach Leaves Using Aqueous Solutions of Biocompatible Ionic Liquids - Ana I. Valente; Ana M. Ferreira; Mafalda R. Almeida; Aminou Mohamadou; Mara G. Freire; Ana P. M. Tavares (Sustainable Chemistry, 2021)
Ribulose-1,5-biphosphate carboxylase/oxygenase (RuBisCO) is the most abundant protein on the planet, being present in plants, algae and various species of bacteria, with application in the pharmaceutical, chemical, cosmetic and food industries. However, current extraction methods of RuBisCO do not allow high yields of extraction. Therefore, the development of an efficient and selective RuBisCOs’ extraction method is required. In this work, aqueous solutions of biocompatible ionic liquids (ILs), i.e., ILs derived from choline and analogues of glycine-betaine, were applied in the RuBisCO’s extraction from spinach leaves. Three commercial imidazolium-based ILs were also investigated for comparison purposes. To optimize RuBisCO’s extraction conditions, response surface methodology was applied. Under optimum extraction conditions, extraction yields of 10.92 and 10.57 mg of RuBisCO/g of biomass were obtained with the ILs cholinium acetate ([Ch][Ac]) and cholinium chloride ([Ch]Cl), respectively. Circular dichroism (CD) spectroscopy results show that the secondary structure of RuBisCO is better preserved in the IL solutions when compared to the commonly used extraction solvent. The obtained results indicate that cholinium-based ILs are a promising and viable alternative for the extraction of RuBisCO from vegetable biomass.